Metal-free oxidative cross-coupling of diazirines with arylboronic acids. Issue 9 (21st December 2015) - Wu, Guojiao; Zhao, Xia; Ji, Wenzhi; Zhang, Yan; Wang, Jianbo
Abstract : The metal-free cross-coupling of diazirines with arylboronic acids under oxidative conditions affords a series of substituted olefins in good yields. Abstract : We report herein a metal-free cross-coupling of diazirines with arylboronic acids under oxidative conditions. The reaction affords a series of substituted olefins. It is proposed that the interaction between the nitrogen on diazirine with arylboronic acid plays a key role in this transformation.